2016
DOI: 10.4028/www.scientific.net/kem.722.44
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Surface Layers of Concrete against Aggressive Environment

Abstract: The article deals with the corrosive effects of acids on the selected surface layers of concrete with/ without an epoxy coating. Concrete sample was placed in extreme environments, which represented the 40% sulphuric acid solution. In addition to measuring surface degradation of concrete, this work focused on the depth of acid penetration into the sample. It can be concluded that the long-term effects of aggressive environments severely degrades the concrete surface on the samples causing corrosion of Type II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have focused on the durability, deterioration, and service life of concrete structures, including numerical models [14][15][16] and experimental studies [17,18]; however, these studies mainly focused on constructions located above ground level and ignored the impact of the different factors on the structures located below ground level. Wei et al [19] investigated how acids coming from the atmosphere and retained in the superficial layers of the ground induce concrete degradation decreasing the compressive strength and increasing the corrosion coefficient of concrete; it was identified that the main reason for premature deterioration of concrete is due to the changes in temperature where the corrosion coefficient was increased about two times for samples exposed to 40 • C. However, the compressive strength results did not show any significant changes during the 90 days of exposition.…”
Section: Causes Of Deterioration Deterioration Typementioning
confidence: 99%
“…Previous studies have focused on the durability, deterioration, and service life of concrete structures, including numerical models [14][15][16] and experimental studies [17,18]; however, these studies mainly focused on constructions located above ground level and ignored the impact of the different factors on the structures located below ground level. Wei et al [19] investigated how acids coming from the atmosphere and retained in the superficial layers of the ground induce concrete degradation decreasing the compressive strength and increasing the corrosion coefficient of concrete; it was identified that the main reason for premature deterioration of concrete is due to the changes in temperature where the corrosion coefficient was increased about two times for samples exposed to 40 • C. However, the compressive strength results did not show any significant changes during the 90 days of exposition.…”
Section: Causes Of Deterioration Deterioration Typementioning
confidence: 99%
“…Materials are exposed to external conditions and physical influences which can lead to unwanted changes in material characteristics and usability, which means their degradation. An example of unfavorable external conditions is temperature changes and/or the presence of aggressive components of the environment 7 .…”
Section: Degradation Of Materialsmentioning
confidence: 99%
“…The overall impact of adverse environmental conditions can result in a degradation process of the building material. The building material then loses its physical, chemical and mechanical properties and stops withstanding environmental influences [7]. The object should then be remediated and reconstructed to stay safe.…”
Section: Introductionmentioning
confidence: 99%